Analisis Pemanfaatan Instagram sebagai Media Promosi Fashion Muslim kepada Gen – Z - Achmad Sulistyono (STES Islamic Village, 2023)
The pervasive influence of social media in contemporary society has spurred its increasing sophistication, making it an indispensable tool for a variety of purposes. Notably, young entrepreneurs have recognized the immense potential of social media platforms, specifically Instagram, as a means to conduct business and promote their products. As the third most popular social media platform, Instagram holds particular appeal for Generation Z users, who frequently rely on it for diverse information, including fashion-related content. This qualitative research endeavor employs an in-depth exploration of the benefits, impacts, and attitudes of Generation Z individuals as Instagram users seeking fashion information from fashion business accounts that leverage Instagram for product promotion. Employing a comprehensive methodology that incorporates observation, interviews, and documentation, this study delves into the multifaceted dynamics of Instagram's utility. The findings reveal the instrumental nature of Instagram as an invaluable resource for Generation Z, while simultaneously examining the positive and negative impacts that ensue. Furthermore, this research delves into the complex attitudes held by Generation Z users, encompassing their emotional states, areas of interest, evaluative judgments, personal experiences, and beliefs concerning Instagram's efficacy as a platform for fashion product promotion